2022
DOI: 10.7554/elife.71074
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic downregulation of neuronal PAS domain 2 (Npas2) promotes surgical skin wound healing

Abstract: Attempts to minimize scarring remain among the most difficult challenges facing surgeons, despite the use of optimal wound closure techniques. Previously, we reported improved healing of dermal excisional wounds in circadian clock neuronal PAS domain 2 (Npas2)-null mice. In this study, we performed high-throughput drug screening to identify a compound that downregulates Npas2 activity. The hit compound (Dwn1) suppressed circadian Npas2 expression, increased murine dermal fibroblast cell migration, and decrease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…The mouse skin wound model has been widely used in investigating hypertrophic scar 48,49 . Herein, we found that ADSCP2 promoted wound healing and attenuated collagen deposition in the mouse model.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The mouse skin wound model has been widely used in investigating hypertrophic scar 48,49 . Herein, we found that ADSCP2 promoted wound healing and attenuated collagen deposition in the mouse model.…”
Section: Discussionmentioning
confidence: 87%
“…The mouse skin wound model has been widely used in investigating hypertrophic scar. 48,49 Herein, we found that ADSCP2 promoted wound healing and attenuated collagen deposition in the mouse model. It has been reported that exosomes secreted from ADSCs promoted hair growth and that the Wnt/β-catenin signaling pathway was activated in ADSC-derived exosome-treated mice.…”
Section: Discussionmentioning
confidence: 88%
“…Further studies have identified circadian control in larger areas of dermal physiology, such as the adequate hydration of the epidermis and stratum corneum ( 25 ), rather than the specific cell types present. In summary, although there is a few evidence in the current literature of Npas2- specific control of dermal wound healing ( 11 , 26 ), there is an extensive publication about the way elements of the circadian system interact with skin physiology to impact wound healing. As such, this study puts forth a novel mechanism by which the circadian system is able to impact cutaneous wounds in order to accelerate dermal wound healing while focusing on the mitigation of excess collagen deposition.…”
Section: Discussionmentioning
confidence: 99%
“…After skin injury, the wound contracts strongly, thereby reducing the wound area. This contraction is caused by the action of myofibroblasts derived from skin fibroblasts and the extracellular matrix regulated by fibroblasts [ 1 , 2 ]. Excessive contraction often causes skin tightness called scar contracture [ 3 ].…”
Section: Introductionmentioning
confidence: 99%